Developing decision support system to redevelop urban facilities (cultural heritage) - ROSMAN, MUHAMMAD SHAKYR (Universiti Teknologi PETRONAS, 2020)
Redeveloping urban facilities, particularly old buildings need a complex decision -making that requires the tangible and intangible values of numerous interest groups. While maintaining the values of heritage buildings, at the same time maximizing the benefits are required in various aspects such as economy, physical condition and environment. Furthermore, with the wide usage of methodological approaches in deciding which criteria are needed to be considered and the best strategy for the reuse of heritage buildings, the needs to process transparent and comprehensive evaluation must be done. Identifying the major criteria and the best alternative by using Analytical Hierarchy Process (AHP) which can converge into a particular interest towards producing a definitive guideline for decision making in redevelopment of heritage buildings.